The representation of Malay-Muslim women’s identity in contemporary Malaysian cinema - Mastura Muhammad (Department of Communications, Universitas Islam Indonesia, 2018)
This paper explores the identity of Malay-Muslim women based on the religious foundation of Islam, feminism and gender in contemporary Malaysian cinema. The number of films produced in the contemporary era between the year of 2000 to the present have portrayed Muslim women characters of fervent spirit and intelligence, possess good values, authoritative, mentally resilient, and independent. Socio-cultural and political changes in Malaysia have encouraged major improvement towards Malay-Muslim women as representational subjects in contemporary Malaysian films. The Malaysian film industry has witnessed an increasing number of films with Islamic content especially towards the end of 1990s. The trend has become popular among Malaysian producers and been well received by the local audience. This scenario indicates a significant relationship between Muslim women and the Islamic related-issue, making it a substantial subject to be examined not only in a social-political context, but also in the cinema studies context. This paper will critically explore the representation of Malay-Muslim women in contemporary Malaysian cinema. The discussion will also consider how their representation intertwined with the religion and customs aspects which subsequently influence a trend in the representation of Malay-Muslim women in contemporary Malaysian cinema.